2012
DOI: 10.1186/1752-153x-6-161
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of textile dyes using immobilized lignin peroxidase-like metalloporphines under mild experimental conditions

Abstract: BackgroundSynthetic dyes represent a broad and heterogeneous class of durable pollutants, that are released in large amounts by the textile industry. The ability of two immobilized metalloporphines (structurally emulating the ligninolytic peroxidases) to bleach six chosen dyes (alizarin red S, phenosafranine, xylenol orange, methylene blue, methyl green, and methyl orange) was compared to enzymatic catalysts. To achieve a green and sustainable process, very mild conditions were chosen.ResultsIPS/MnTSPP was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…Bleaching percentages were high as 82% after one hour of reaction[57], in agreement with our results for supported MnP1 obtained at a MnP/oxidant/dye molar ratio of 1:5000:10 (MnP1-S-Mag 81% dye bleaching and MnP1-Hallo…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Bleaching percentages were high as 82% after one hour of reaction[57], in agreement with our results for supported MnP1 obtained at a MnP/oxidant/dye molar ratio of 1:5000:10 (MnP1-S-Mag 81% dye bleaching and MnP1-Hallo…”
supporting
confidence: 93%
“…Here, the pH of the bleaching reaction lay between 6 and 7. Comparison of the present work with the work by Zucca et al [57] showed that this MnP with similar structure efficiently catalyze bleaching reactions.…”
Section: Catalytic Oxidation Reactionssupporting
confidence: 52%
See 1 more Smart Citation
“…Lignin (LiP) and manganese peroxidase (MnP) exhibit similar reaction mechanism. Recently, Zucca and co-workers [196] demonstrated as two immobilized metallo-porphirine (structurally similar to the ligninolytic peroxidase) to bleach six different dyes. The two different enzymes effectively bleached all tested dyes working in mild operating conditions (standard pressure, room temperature and neutral pH, using no organic solvents).…”
Section: Dyesmentioning
confidence: 99%
“…In our previous studies, we reported the immobilization of some metalloporphins onto solid supports emulating the structure of cytochrome P-450 and ligninolytic peroxidases. These catalytic adducts were able to oxidize both lignin model compounds (recently reviewed in [26]) and durable textile dyes [27][28][29].…”
Section: Introductionmentioning
confidence: 99%